Учимся работать на компьютере - Антошин Максим Константинович (Внимание: дети!, 2005)
Экземпляры: аб. ЦБ (2006) / Инвентарный номер: 52330 / Цена: / Сис.шифр: 32.973 / Авт.знак: А 72 / ГРНТИ: 47 / ББК: 32.973